Clinical Use of an Electronic Pre-Visit Questionnaire Soliciting Patient Visit Goals and Interim History: A Retrospective Comparison Between Safety-net and Non-Safety-net Clinics - Hannah Shucard MS; Emily Muller MD; Joslyn Johnson BS; Jan Walker RN, MBA; Joann G. Elmore MD, MPH; Thomas H. Payne MD; Jacob Berman MD MPH; Sara L. Jackson MD, MPH (SAGE Publishing, 2022)
Introduction/Objectives We examined an initial step towards co-generation of clinic notes by inviting patients to complete a pre-visit questionnaire that could be inserted into clinic notes by providers and describe the experience in a safety-net and non-safety-net clinic. Methods We sent an electronic pre-visit questionnaire on visit goals and interim history to patients at a safety-net clinic and a non-safety-net clinic before clinic visits. We compared questionnaire utilization between clinics during a one-year period and performed a chart review of a sample of patients to examine demographics, content and usage of patient responses to the questionnaire. Results While use was low in both clinics, it was lower in the safety-net clinic (3%) compared to the non-safety-net clinic (10%). We reviewed a sample of respondents and found they were more likely to be White compared to the overall clinic populations ( p  < 0.05). There were no statistically significant differences in patient-typed notes (word count and number of visit goals) between the safety-net and non-safety-net samples however, patients at the safety-net clinic were less likely to have all of their goals addressed within the PCP documentation, compared to the non-safety-net clinic. Conclusions Given potential benefits of this questionnaire as a communication tool, addressing barriers to use of technology among vulnerable patients is needed, including access to devices and internet, and support from caregivers or culturally concordant peer navigators.